Eco-friendly incombustible biocomposite and method for preparing the same - JEONG NAM JO; YOU YOUN JONG; KIM HEE YEON; HAN SEONG OK (2014)
Disclosed is an eco-friendly incombustible biocomposite including: a) a polymer matrix comprising a natural fiber; and b) a ceramic sheet laminated integrally with the polymer matrix. The biocomposite is eco-friendly since the natural fiber is used as a reinforcement material and is incombustible since it is laminated integrally with the ceramic sheet. Further, it has superior storage modulus, dimensional stability and flexural properties and lightweightness, and is processable into various structures. Thus, it is very useful for automotive or building indoor/outdoor materials.